The Racialized Impact of Study Abroad on US Students' Subsequent Interracial Interactions. (1st December 2014) - Lowe, Maria R.; Byron, Reginald A.; Mennicke, Susan
Abstract : Using an online survey of American undergraduate students, this paper serves as a case study of a liberal arts college located in the Southern United States (US) to explore the effects of studying abroad on students' attitudes and behavior related to diversity upon their return to campus. We find that white students and students of color report significantly different study abroad experiences and distinct patterns related to their likelihood to engage with racial, but not other forms of, diversity when they return to their home university. Specifically, students of color are more likely than white students to report that their study abroad experiences have increased the likelihood that they interact more frequently with individuals from different racial backgrounds in a number of campus contexts. Utilizing existing literature and our qualitative data, we address possible reasons for these racialized patterns.